Panglima: Sosok Pemimipin Ideal dalam Pandangan Masyarakat Dayak (Diskursus Filosofis Berdasarkan Pemikiran Machiavelli terhadap Kepemimpinan Panglima Jilah, Pemimpin Pasukan Merah Tariu Borneo Bangkule Rajakng) - Fransesco Agnes Ranubaya; Dominikus Irpan; FX. Eko Armada Riyanto; Yohanes I Wayan Marianta (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2024)
The focus of this paper is a philosophical discourse on the figure of the Panglima as an ideal leader in the beliefs of the Dayak people based on Marchiavelli's thoughts in his work,